Lability of Pb in soil: effects of soil properties and contaminant source - Mao, Lingchen; Bailey, Elizabeth H.; Chester, Jonathan; Dean, Joseph; Ander, E. Louise; Chenery, Simon R.; Young, Scott D. (CSIRO Publishing, 2014)
Environmental Context: There is growing concern that lead (Pb) in the environment may cause adverse health effects in human populations. We investigated the combined use of isotopic abundance and isotopic dilution to show how the origins of soil Pb and soil characteristics affect lability. Soil pH and soil Pb content are the dominant controls on Pb lability; the lability of recent petrol-derived Pb is similar to that of other sources in urban soils but greater than geogenic Pb in rural roadside topsoils. Lability of lead (Pb) in soils is influenced by both soil properties and source(s) of contamination. We investigated factors controlling Pb lability in soils from (i) land adjacent to a major rural road, (ii) a sewage processing farm and (iii) an archive of the geochemical survey of London. We measured isotopically exchangeable Pb (E-values; PbE), phase fractionation of Pb by a sequential extraction procedure (SEP) and inferred source apportionment from measured Pb isotopic ratios. Isotopic ratios (206Pb/207Pb and 208Pb/207Pb) of total soil Pb fell on a mixing line between those of petrol and UK coal or Pb ore. The main determinant of the isotopically exchangeable Pb fraction (%E-value) was soil pH: %E-values decreased with increasing pH. In rural roadside topsoils and there was also evidence that, petrol-derived Pb remained more labile (35%) than Pb from soil parent material (27%). However, in biosolid-amended and London soils %E-values were low (c. 25%), covered a restricted range, and showed no clear evidence of source-dependent lability.